The Effectiveness of the Verbal Quiz Method in Enhancing Vocabulary Mastery - Aprialiana, Titin; Kalsum, Kalsum; Rustam, Utary (JELITA, 2025)
This study aims to evaluate the effectiveness of the verbal quiz method in improving the vocabulary ability of grade VIII students at SMPN 2 Patampanua. This study used a pre-experimental design with one group pre-test and post-test. The population of this study was class VIII students at SMPN 2 Patampanua, and the sample selected was class VIII.2 consisting of 26 students. The research indicated a significant increase in students’ vocabulary ability after the treatment. The average score of students on the pre-test was 45.23, with a standard deviation of 9.64, while the average score on the post-test increased to 68.76, with a standard deviation of 15.63. The t-test value reached 6.34, higher than the t-table value of 1.708 at a significance level of 0.05 with 25 degrees of freedom. Based on the assessment rubric during the treatment, improvements were seen in several aspects, including appropriate vocabulary, speaking fluency, context understanding, and pronunciation. These results show that the increase in the average score from 37.5 in the second meeting to 60.3 in the fifth meeting shows significant improvement. Based on these findings, the writer concluded that students' vocabulary ability improved in several aspects, such as appropriate use of vocabulary, fluency, context understanding, and pronunciation, after being given the application of the verbal quiz method, which can effectively improve the vocabulary ability of grade VIII students at SMPN 2 Patampanua.